Polysplenia and other anatomical variants of the spleen - Agnieszka Kopystecka; Justyna Lipińska; Izabela Kopeć; Łukasz Lipiński; Magdalena Woźniak; Grzegorz Jędrzejewski (Kazimierz Wielki University, 2022)
The anatomy, physiology and embryology of the spleen are essential fields of study for the determination of congenital varieties as well as the pathological processes occurring in this organ.The aim of this study is to summarize the current knowledge on the proper development of the spleen and to present structural variants that may be of clinical significance or be important from the radiologist's point of view.Structural changes of the spleen may result in non-specific clinical symptoms, which may confuse an inexperienced physician. Inaccurate diagnosis and late diagnosis have various negative, often even fatal, consequences. In order to make an appropriate diagnosis, and thus help the patient in a timely manner, it is necessary to have extensive knowledge about the variants of the structure of the spleen. Knowledge of anatomical variations is essential for the development of a differential diagnosis, which enables the correct diagnosis to be made.